Inovações tecnológicas na elaboração da cartografia: uso do GNSS/RTK e drone para fins de regularização fundiária urbana - COSTA, Antonio Cleison de Souza (2022)
The work reflects on the application of technological innovations for the making of cartography, with the use of GNSS RTK and Drone, applied to land regularization and its resonances in territorial management as a technical assistance tool to reduce urban socio-environmental nonconformities. In this way, in the planialtimetric survey, elements are sought that can integrate the management and use of the soil through the benefits that integrate the actions of the Amazon Network Program in assistance to land regularization. In this way, the objective is to insert GNSS RTK and Drone as elements of spatial analysis as integration tools, which drives to overcome urban, environmental and sociopolitical challenges. The methodology applied had a descriptive and exploratory character of Povoado Josias, municipality of Zé Doca, in the State of Maranhão, based on documentary, bibliographic and field reconnaissance, aerial survey and reambulation. The results were satisfactory for the feasibility of using the technological tools, as it is a methodology that optimizes the survey execution time, when compared to the conventional one, and reduces labor in the field execution and in the construction of the cartography of the existing installment. It is worth mentioning that the field methodology has become acceptable for the current pandemic moment, as it avoids and reduces contact with the community, being a way of guaranteeing the safety and health of those involved. In addition, the cartography will help in the management of access to the democratization of space and the quality of life in the city.